Verbal and Non-Verbal Signs of “Moana Movie Poster - Andhika Dhananjaya, Putu (Humanis; Vol 23 No 1 (2019)DO - 10.24843/JH.2019.v23.i01.p08, 2019)
The study is entitled Verbal and Non-Verbal Signs of “Moana” Movie Posters. This study focused on the analysis of verbal and non-verbal signs of “Moana” movie poster and the meaning of those signs. It was aimed at identifying the verbal and non-verbal signs found in “Moana” movie posters. It was also aimed at explaining the meaning of verbal and non-verbal signs in those movie posters. The data of this study were taken from the websites namely www.impawards.com . The data were collected using the documentation method. Then, the collected data were qualitatively and descriptively analyzed based on the theories applied in this study, namely the theories of semiotics proposed by Saussure, theory of verbal and non-verbal signs proposed  by Dyer, and supported with the theory of color terms proposed by Wierzbicka, and theory of color meaning proposed by Eisman. The result of analysis shows that “Moana” movie posters have verbal and non-verbal signs. The verbal signs are “Disney”, “Moana”, “Sing with Moana!”, “Sing-Along”, “Special Sing-Along Engagement”, “January 27 th in Select Theatres Nationwide”, “Soundtrack Available Now”, “From the Creators of Zootopia and Frozen”, “November 23”, “In 3D and Real D 3D”, “The Ocean is Calling”, Dwayne Johnson as Maui”, and “Auli’i Cravalho as Moana”. Those verbal signs provide the information about the title, release date, movie quality, the information of actor and actress as voices over, the information about the soundtrack of the movie, as well as company and creator that produced the movie. Then, the non-verbal signs consist of shape, appearance, manner activity, background, and color.